Influencia Del Hábito De La Lectura En La Enseñanza Aprendizaje Del Vocabulario En Estudiantes De Octavo Año De Educación Básica - Liliana, Cando Carrillo María; Alexandra, Chuquimarca Once Doris; Luis Even, Pazmiño Pavón (European Scientific Journal, ESJ, 2018)
The objective of the research was to determine the reasons why eighth year parallel "A" students of Primary Education at the "Maldonado High School” do not improve their vocabulary during the learning process through reading. To do so, the types of reading that the teacher uses in classes were diagnosed; we identified the techniques used to teach vocabulary and finally proceeded with the inference of reasons because students lack vocabulary when they read. The research was diagnostic and the ethnographic method was used to describe and analyze the sociocultural environment of the research context. The sample was intentional and represent twenty-eight students and one teacher. The data were obtained by means of participatory observation with an observation list, applied in May and June of 2016. The research was inductive and field, as general conclusions were obtained from observation, classification and study of facts, based on the direct collection of information from the reality in which it was investigated. The results obtained were tabulated, analyzed and interpreted and determined that students have a bad habit and do not follow a technical reading process.